The Effect Of Work Motivation, Leadership Style And Work Stress On Performance - Neksi Widi HERMAN; Zahara Tussoleha RONY; Faroman SYARIEF (International Journal of Environmental, Sustainability, and Social Science, 2022)
The performance of organizational members supports personnel in carrying out all the tasks that are their responsibility. If a person works for work, can complete the given on time, can always contribute, and has a good attitude and behavior under the work standards set by the organization and the values ??prevailing in the environment and leadership factors are something else that cannot be done. Each person’s performance will not be separated from a person’s ability and the organization’s work environment in which they work. Separated from the development of police institutions (including the National Police Research and Development Agency). The research method used in this study is a quantitative method with the SPSS causal survey software. Research design research data collection through field observations, surveys, and direct interviews with related parties. The population in this study were members of the Jianbang Bureau of the National Police Training Center. The sampling technique in this study uses a saturated sampling technique with a total of 106 members. The study results explain that work motivation has a significant effect on performance. Leadership style has a considerable influence on personnel performance. There is insufficient evidence that job stress has a significant negative impact on work performance and motivation; leadership style and work stress simultaneously significantly affect employee performance.